The Effect Of Crumb Rubber Fine Aggregate Replacements On The Flexural Performance Of Fibre Reinforced Concrete Beams - Alasmari, Hasan (2019)
It is well known that crumb rubber when incorporated in concrete has shown an improvement in elastic properties which actually enhance the energy absorption. However, the static responses of fibre at different aspect ratios incorporated with crumb rubber aggregate in a double layer are yet to be investigated. This study investigates the effect of crumb rubber aggregates with and without steel fibres on the flexural behaviour of layered and non-layered reinforcement concrete beams on a full scale. Rubberized concrete of layered and non-layered specimens were prepared by partial replacement of 10%, 12.5%, and 15% of sand aggregate volumes. Fibrous concrete were prepared from different types of aspect ratios of steel fibres (80 and 60) with different lengths for hooked-end and micro copper coated steel fibres at a 0.5% of the volume fractions. The layered specimens were constructed by placing rubberized concrete at the top and both layers, whilst the bottoms were dedicated to fibrous concrete. The non-layered specimens were prepared using a combination of rubberized and fibrous concrete subjected to their aspect ratios. The static responses were evaluated in terms of their fresh properties and beam characteristics’ behaviour. The findings revealed that the layering enhanced the mechanical properties’ performances compared to the non-layered samples. Increasing the aspect ratios of the steel fibres with inclusion of the crumb rubber aggregate led to increase in flexural strength and stiffness of the beams, whilst the lower aspect increases the toughness, ultimate deflection, ductility index and strain. Furthermore, the newly developed layered beams helped for further cracking control and enhanced the failure patterns. Overall, the results have shown promising performance in the layered form whether in beams or standard specimens.